Promising wing vibration measurement system using MEMS IMUS and Kalman filter correction - Afonin, Alexander A.; Sulakov, Andrey S.; Maamo, Shikho M. (Zielona Góra: Uniwersytet Zielonogórski)
Nowadays, there is still a need for the development of a high-precision vibration measurement system for aircraft wings. By analyzing the wing vibration characteristics a lot of aviation studies could be conducted, including the wing health monitoring, the fluttering phenomenon and so on.
Keywords: Aircraft wing; vibration measurement; Kalman filters; MEMS IMU; closed-loop optimal correction